Cooperative jamming and power allocation with untrusty two‐way relay nodes. Issue 13 (1st September 2014) - Long, Hang; Xiang, Wei; Wang, Jing; Zhang, Yueying; Wang, Wenbo
Abstract : This study investigates the security of the two‐way relaying system with untrusty relay nodes. Cooperative jamming schemes are considered for bi‐directional secrecy communications. The transmit power of each source node is divided into two parts corresponding to the user and jamming signals, respectively. Two different assumptions of the jamming signals are considered. When the jamming signals are a priori known at the two source nodes, closed‐form power allocation expressions at two source nodes are derived. Under the assumption of unknown jamming signals, it is proven that the cooperative jamming is useless for the system secrecy capacity, because that all the power should be allocated to the user signals at each source node. Relay selection is also investigated based on the analysis of cooperative jamming. Simulation results are presented to compare the system secrecy capacities under the two jamming signal assumptions.